ANALISIS PERBEDAAN IMPLEMENTASI PSAK NO. 14 TENTANG PERSEDIAAN SEBELUM DAN SESUDAH KONVERGENSI IFRS DAN PENGARUHNYA TERHADAP LABA PERUSAHAAN - Puspasari, Dina Afrilia; Halim, Abdul; sulistyo, sulistyo (Jurnal Riset Mahasiswa Akuntansi, 2016)
The purpose of this research is to analyze the significant difference of the implementation Pernyataan Standar Akuntansi Keuangan (PSAK) No. 14 about inventory and profit before and after IFRS (International Financial Reporting Standard) convergence for 18 commerce companies listed Indonesian Stock Exchange between 2011 and 2012. The author applies secondary data from annual financial reports. The analysis model is event study. The method applies paired samples t-test. The result indicates that there is significant difference in inventory and profit before and after IFRS convergence.